(untitled) (Marketing Journal, 2025)
This article explores the development processes of the tourism sector in regions of the Republic of Uzbekistan with high investment attractiveness. Using the examples of Tashkent city, Samarkand, Bukhara, Khorezm (Khiva), and the Fergana Valley, the articl e analyzes development indicators in areas such as infrastructure modernization, service quality, eco -agro tourism, marketing, and international cooperation. It also 548 examines the challenges faced in tourism development within these regions and analyzes the existing potential and forward -looking proposals. The article concludes with practical recommendations for ensuring the sustainability of these trends.